Associations between the HLA-A/B/DRB1 polymorphisms and aplastic anemia: evidence from 17 case–control studies. Issue 3 (16th March 2018) - Deng, Xiao-Zhen; Du, Meng; Peng, Jiao; Long, Jian-Xiong; Zheng, Cheng-Jun; Tan, Yuan; Li, Li-Juan; Chen, Hui-Ying; Qing, Cao; Pang, Yan-Yan; Lan, Yan; Zhang, Hai-Tian
ABSTRACT: Objective: To estimate the associations between HLA-A/B/DRB1 polymorphisms and aplastic anemia (AA), we carried out the meta-analysis. Methods: In this meta-analysis, all publications in English and Chinese were considered up to 30 September 2015. The electronic databases we searched were Pubmed, Science Direct, Embase, Web of Science, CNKI, Wanfang Data and VIP. We conducted all statistical data analyses in the Stata11.0 software. Results: A total of 17 studies including 9164 subjects (containing 1372 cases and 7792 controls) were retrieved, which studied the relationship between HLA-A/B/DRB1 and AA. Odds ratios (ORs) with 95% confidence intervals (CIs) for the comparisons between cases and controls were calculated. The result revealed that HLA-A*02 and HLA-DRB1 (*0407, *15 and *1501) polymorphisms might increase the risk of AA. Otherwise, HLA-DRB1 (*0301, *04, *0406, *0802, *1301, *1302 and *14) were protective against AA. But, other sites of HLA-A/B/DRB1 in our study had no correlations with AA (all P c  > 0.05). Conclusion: In conclusion, HLA-A/B/DRB1 polymorphisms may play an important role in AA, but higher quality and larger sample studies are needed to confirm.